Scleromyxedema, a therapeutic dilemma - Salas-Alanis, Julio Cesar (Indian J Dermatol, 2015)
Scleromyxedema is characterized by indurated erythematous papules disseminated on the face, chest and limbs. About twenty cases treated with thalidomide, stem cells, melphalan and immunoglobulin with varying results have been described. We present the case of a 28-year-old male patient diagnosed with scleromyxedema not associated with monoclonal gammopathy, multi-treated with anti-leprosy drugs, UVA1, and thalidomide for 4 years with no improvement.